Plasma Calprotectin Is Predictive for Short-Term Functional Outcomes of Acute Ischemic Stroke - Hu, Zicheng; Li, Haihua; Zhu, Yongping; Zhang, Jun; Yang, Xiao; Huang, Rongzhong; Li, Yongyong; Ran, Haitao; Shang, Tingting (Frontiers in Neurology, 2022)
Background Blood-based prognostic biomarkers of acute ischemic stroke (AIS) are limiting. Calprotectin is suggested to be involved in directing post-stroke inflammatory conditions. However, the pathological alteration of circulating calprotectin in AIS is yet to be thoroughly elucidated. Therefore, this study aimed to investigate the levels and clinical relevance of calprotectin in AIS. Methods This study recruited 271 patients with AIS within 24 h since symptom onset and 145 non-stroke healthy controls (HC) from February 1, 2018, to Dec 31, 2020. Patients were followed up for 2 weeks for observation of functional outcomes, as determined by the National Institutes of Health Stroke Scale (NIHSS) and modified Rankin Scale (mRS). Plasma calprotectin concentrations were determined by ELISA. Results Plasma calprotectin concentrations were significantly higher in patients with AIS compared with controls [patients vs. control: median (IQR) 54.2 (39.01–99.04) vs. 50.04 (35.42–61.22), p < 0.001]. Besides, patients with poor prognosis, as defined by mRS ≥ 3, had significantly higher calprotectin levels than patients with good prognosis [poor prognosis patients vs. good prognosis patients: median (IQR) 61.99 (47.52–108) vs. 43.36 (33.39–60.2), p < 0.001]. Plasma calprotectin levels were positively associated with the disease severity of AIS, as reflected by infarction volume and NIHSS score at baseline. Furthermore, baseline calprotectin was found to be independently associated with poor prognosis [odds ratio (OR): 1.02, 95% CI: 1.01–1.03] and disease progression (OR: 1.03, 95% CI: 1.02–1.04) of AIS during a 2-week follow-up, with adjustment of possible confounding factors. Conclusion Plasma calprotectin is associated with short-term functional outcomes of AIS.